Conocimientos y prácticas de enfermedad diarreica aguda en madres de niños menores de 5 años, Subcentro de Salud Catacocha Guido Alfonzo Díaz Jumbo - Pogo Guamán, Rosa María (2018)
Acute Diarrheal Disease, it is the second cause of death in children under the age of five, it is a disease that can be prevented by access to drinking water and to adequate sanitation and hygiene services, according to the World Health Organization in its publication of facts and figures in 2017. The present investigation was proposed To determine the knowledge and practices about the Acute Diarrheic Disease in mothers of children under the age of five who attend the Subcentro de Salud Catacocha Guido Díaz. It was a descriptive and transversal study; the universe consisted of 4,200 mothers, from which a sample of 352 mothers who attended the Subcentro de Salud was obtained, during the period September 2017 - March 2018. The technique used for the collection of information was the survey. Which results determine that in what regards to the knowledge show that mothers do not clearly define this pathology, they do not know the causes that can originate it, but they recognize the signs and symptoms to take their children to the doctor in a timely manner. In what regards to practices, they mostly provide exclusive breastfeeding, they perform hand washing before handling food as a preventive measure, self-medication with antibiotics and over-the-counter pharmaceutical products stands out. Key words: Knowledge, Practices, Acute Diarrheal Disease.